2017
DOI: 10.17488/rmib.38.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Collagens for Tissue Engineering Scaffolds

Abstract: Las colágenas son cada día más atractivas en la fabricación de andamios para Ingeniería de Tejidos, por su biocompatibilidad, manejo y capacidad de producirlas industrialmente. El objetivo del presente artículo fue presentar un análisis sobre el avance en la investigación, el desarrollo y producción de colágenas recombinantes de humano, los sistemas de producción y sus usos en Ingeniería de Tejidos. Se realizó una revisión de la literatura científica internacional arbitrada en bases de datos como Scopus, PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Also, Jangamreddy et al (2018), employing collagen-like-peptides conjugated with polyethylene glycol, made implants that were grafted into miniature-pig corneas to study their effects on corneal regeneration; their results suggested that the implant acts as a promotor of corneal tissue regeneration [24]. While the results are encouraging, besides inefficiency under certain conditions or undesired side effects, the most promising synthetic corneas require expensive reagents, such as recombinant human collagen or peptides, making it impossible for people from middleand/or low-income countries to acquire them [28,29]. Thus, developing corneal substitutes using low-cost reagents is a pivotal task to reach the translation to a broad public.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Jangamreddy et al (2018), employing collagen-like-peptides conjugated with polyethylene glycol, made implants that were grafted into miniature-pig corneas to study their effects on corneal regeneration; their results suggested that the implant acts as a promotor of corneal tissue regeneration [24]. While the results are encouraging, besides inefficiency under certain conditions or undesired side effects, the most promising synthetic corneas require expensive reagents, such as recombinant human collagen or peptides, making it impossible for people from middleand/or low-income countries to acquire them [28,29]. Thus, developing corneal substitutes using low-cost reagents is a pivotal task to reach the translation to a broad public.…”
Section: Introductionmentioning
confidence: 99%